Eco-friendly blast furnace iron runner hot-state repairing material and preparation and use methods thereof
By adopting eco-friendly blast furnace iron groove hot repair materials including blast furnace iron slag, electromelting reinforced corundum and other raw materials, and optimizing process parameters, the problems of short service life and long baking time of traditional repair materials are solved, and the rapid baking and high adhesion of repair materials are achieved, which significantly improves service life and economic benefits.
Patent Information
- Application Number
- CN202510170690.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional blast furnace iron groove hot repair materials have a short service life in harsh environments, which is difficult to meet the needs of continuous and stable production, and the baking time is long and cannot be repaired quickly, which has the risk of increasing phosphorus in molten iron affecting the quality of steel products.
Eco-friendly blast furnace iron groove hot repair materials are used, and their raw materials include blast furnace iron slag, electromelting reinforced corundum, silicon carbide, modified asphalt, carbon black, alumina powder, metal aluminum powder, metal silicon powder, explosion-proof fiber and polymer aluminum oxalate sol. By controlling the particle size and addition of raw materials, process parameters are optimized to achieve rapid baking and high adhesion.
It achieves rapid baking and bursting of repair materials, high strength, good overall performance during use, excellent slag corrosion resistance, long service life, and significant social and economic benefits.
Smart Images

Figure BDA0005273935640000061 
Figure BDA0005273935640000062 
Figure BDA0005273935640000063
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steelmaking and refractory materials, and in particular to an eco-friendly blast furnace iron ditch hot repair material and a preparation and use method thereof. Background Art
[0002] In the field of steel smelting, blast furnace ironmaking is a key link. With the development of the industry, large-scale blast furnaces and intensified smelting have become a trend. Although this has improved production efficiency, it has also brought severe challenges to the key facilities in the ironmaking process - the refractory materials of the working layer of the ironmaking yard. The amount of slag iron has increased significantly, and the temperature of slag iron has increased significantly, and the use environment of the refractory materials of the working layer of the ironmaking yard has become increasingly harsh. Its internal lining has been subjected to strong scouring and erosion by high-temperature slag iron for a long time, which not only affects the service life of the refractory materials, but also becomes an important factor restricting the safe production of ironmaking.
[0003] The traditional baking-free ramming material has a short service life in such an environment and cannot meet the needs of continuous and stable ironmaking production. Frequent replacement of ramming materials not only increases production costs, but also affects production efficiency due to shutdowns for maintenance, resulting in economic losses. Although the use of cement-bonded gunning materials can repair damaged iron grooves to a certain extent, its baking time is relatively long. For small and medium-sized blast furnaces, it is crucial to put them into use as soon as possible after rapid repair. Excessive baking time makes cement-bonded gunning materials unable to meet this requirement, limiting their application in iron groove repair of small and medium-sized blast furnaces.
[0004] In addition, there are also problems with the spray coating combined with aluminum dihydrogen phosphate. Because impurity elements are introduced into the binder, there is a risk of phosphorus increase in the molten iron during use. Phosphorus increase in molten iron will increase the intensity of subsequent molten iron pretreatment, which not only increases production costs, but may also affect the quality of the final steel product.
[0005] At present, the market is in urgent need of a new type of blast furnace iron ditch hot repair material that can adapt to the harsh working environment of the blast furnace and overcome the various defects of traditional repair materials. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an eco-friendly blast furnace iron groove hot repair material and its preparation and use method. The present invention can better solve the above problems, has the characteristics of being friendly to the ecological environment, good adhesion, good bonding with the hot groove lining, can be quickly baked without bursting, has high strength and good overall performance during use, excellent slag erosion resistance, long service life, and has significant social and economic benefits.
[0007] To achieve the above object, the present invention is implemented by the following technical solutions:
[0008] In a first aspect, the present invention provides an eco-friendly blast furnace iron channel hot repair material, wherein the raw materials of the repair material include a main material and additional explosion-proof fibers and polymerized aluminum oxalate sol;
[0009] The main material includes the following raw materials by weight percentage: 15-23% blast furnace slag, 34-60% fused reinforced corundum, 12-20% silicon carbide, 1-5% modified asphalt, 2-6% carbon black, 7-10% alumina powder, 1.5-3% metal aluminum powder, and 1.5-3% metal silicon powder;
[0010] Based on the weight of the main material, the explosion-proof fiber accounts for 0.04-0.12% of the weight of the main material, and the polymerized aluminum oxalate sol accounts for 10-16% of the weight of the main material.
[0011] As a further optimization scheme of the present invention, the main material includes the following raw materials in weight percentage: 15% blast furnace slag, 54% fused reinforced corundum, 15% silicon carbide, 1.5% modified asphalt, 3% carbon black, 8% alumina powder, 2% metal aluminum powder, and 1.5% metal silicon powder; the explosion-proof fiber accounts for 0.06% of the weight of the main material, and the polymerized aluminum oxalate sol accounts for 12% of the weight of the main material.
[0012] As a further optimization scheme of the present invention, the mass percentage of CaO in the blast furnace slag is 38-42%, the mass percentage of SiO2 is 30-35%, the mass percentage of Al2O3 is 14-17%, and the mass percentage of MgO is 6-9%; the particle size range of the blast furnace slag includes 3mm≤particle size≤5mm and 1mm≤particle size≤3mm, wherein the blast furnace slag with 3mm≤particle size≤5mm accounts for 25-30% of the total mass of the blast furnace slag, and the blast furnace slag with 1mm≤particle size≤3mm accounts for 40-50% of the total mass of the blast furnace slag.
[0013] When the particle size is ≥5mm, the construction quality will deteriorate and the performance will be reduced. The weight percentage of blast furnace slag of each particle size exceeding the above range will directly affect the particle size grading of the repair material, and then affect the construction performance and performance of the product. Blast furnace slag can generate carbides and nitrides under a reducing atmosphere, and improve the high-temperature physical properties of the repair material through fiber reinforcement, thereby increasing the service life of the iron ditch. In addition, after recycling, blast furnace slag is conventionally used as one of the raw materials for the production of silicate cement, with low added value; this technology uses it as a refractory raw material, which can not only save resources and protect the environment, but also increase the sintering performance and thermal stress shock resistance of the repair material during use, but also increase its added value and create higher economic value.
[0014] As a further optimization scheme of the present invention, the mass percentage of Al2O3 in the fused corundum is ≥92%, and the mass percentage of TiO2 is 3-5%; the particle size range of the fused corundum includes 1mm≤particle size≤3mm, 0.088mm≤particle size≤1m and 0mm≤particle size≤0.088mm, among which the fused corundum with 1mm≤particle size≤3mm accounts for 28-36% of the total mass of the fused corundum, the fused corundum with 0.088mm≤particle size≤1mm accounts for 23-30% of the total mass of the fused corundum, and the fused corundum with 0mm≤particle size≤0.088mm accounts for 34-49% of the total mass of the fused corundum.
[0015] When the particle size is ≥3mm, it will affect the overall particle size distribution of the repair material and the material toughness during high-temperature use. If the weight percentage of each particle size of fused reinforced corundum exceeds the above range, it will directly affect the particle size distribution and physical strength of the repair material, and then affect the construction performance and use performance of the product. In a reducing atmosphere, fused reinforced corundum can react with the carbon source in the repair material, carbon and nitrogen in the molten iron, etc. to generate titanium carbide and titanium nitride, and by forming a protective film on the surface of the fused reinforced corundum particles, the anti-corrosion and anti-permeation properties are enhanced, thereby improving the performance and life of the iron channel.
[0016] As a further optimization scheme of the present invention, the mass percentage of SiC in the silicon carbide is ≥97%, and the silicon carbide particle size range includes 0.088 mm ≤ particle size ≤ 1 mm and particle size ≤ 0.088 mm, wherein the silicon carbide with a particle size of 0.088 mm ≤ ≤ 1 mm accounts for 30-50% of the total mass of the silicon carbide, and the silicon carbide with a particle size of ≤ 0.088 mm accounts for 50-70% of the total mass of the silicon carbide. The addition of the silicon carbide can improve the corrosion resistance, thermal shock resistance and wear resistance of the repair material.
[0017] As a further optimization scheme of the present invention, the bulk density of the modified asphalt is 1.05-1.15 g / cm 3 , viscosity is 20~40Pa·s, softening point is 105~120℃, flash point ≥230℃, coking value ≥54%, particle size 0.088mm≤≤0.5mm.
[0018] The modified asphalt can be stably stored for more than 3 months, and its durability reaches 5 to 20 years. 3, viscosity 100~3000Pa·s, softening point 65~95℃), it has stronger adhesion, higher stability and better durability. Controlling the softening point of asphalt powder can better meet the requirements of on-site construction and baking. Controlling the coking value can ensure that the repair material has sufficient strength after baking, so as not to collapse or crack due to improper strength and operation; at the same time, it can control the concentration of volatile components generated by the repair material during baking, reducing pollution to the environment and harm to the health of employees.
[0019] As a further optimization scheme of the present invention, the mass percentage of C in the carbon black is ≥99%, the carbon black particle size is 10nm≤particle size≤100nm, and the specific surface area is greater than 1000m 2 / g. The introduction of nano carbon black can significantly improve the strength and stiffness of the material, making it have better wear resistance and high temperature resistance.
[0020] As a further optimization scheme of the present invention, the mass percentage of Al2O3 in the alumina micropowder is ≥99.5%, the d50 of the alumina micropowder is 4.2 μm, d10 is 1.1 μm, d90 is 12.1 μm, and the typical value of the specific surface area is 10.8 m 2 / g. This alumina powder has a wide range of particle sizes and a large specific surface area. It can not only increase the sintering of the repair material at high temperatures and improve its high-temperature performance, but also replace the addition of silicon powder and clay in conventional repair materials to increase the shaping and viscosity of the repair material and reduce the risk of generating low-melting products at high temperatures.
[0021] The metal aluminum powder and metal silicon powder, when added to the carbon-containing refractory material, can undergo reactions such as carburization and nitridation during use, generating a large amount of non-oxide reinforcement phase in situ, transforming the structure of the material into a mainly non-oxide bond, while also helping to reduce the oxidation of the carbon source in the repair material, greatly improving the high-temperature performance of the material.
[0022] As a further optimization scheme of the present invention, the explosion-proof fiber is polyethylene fiber, with a melting point of 100-120°C, a length of <6mm, good dispersibility and corrosion resistance, and little effect on the fluidity of the castable, which can effectively solve the baking cracking problem, shorten the baking time, and achieve rapid baking. The main structure of the polymerized aluminum oxalate sol is aluminum oxycarboxylate, with a mass percentage of Al2O3>30%, high concentration and high viscosity. Compared with other sols, it can reduce the free water and structural water in the material (such as the mass percentage of Al2O3 in alumina sol is 20-24.8%; the mass percentage of SiO2 in silica sol is 20-30%, and the kinematic viscosity is about 4-8mm 2 / s), significantly improving the bonding strength of the material; the polymerized aluminum oxalate sol has good stability and good affinity for aqueous solutions, and does not require the addition of a water reducer. After dehydration, it can form a stable three-dimensional network structure, thereby enhancing the stability of the repair material.
[0023] In a second aspect, the present invention further provides a method for preparing and using the eco-friendly blast furnace iron groove hot repair material, comprising:
[0024] Preparation of dry materials: The ingredients are prepared according to the composition and content of the raw materials. First, the matrix material with a particle size of less than 0.088 mm and the explosion-proof fiber are uniformly mixed for 2 to 3 minutes, and then the mixed matrix material is added to the aggregate with a particle size of more than 0.088 mm, stirred for 3 to 5 minutes, and mixed evenly, and then packaged in half-ton bags for standby use; the process of uniformly mixing for 2 to 3 minutes can effectively reduce the phenomenon of uneven mixing of important raw materials in the repair material, and avoid the adverse effects of process defects on the construction performance and use performance of the product;
[0025] When using, first pour the dry material into the mixer, add 3-4% polyaluminium oxalate sol for premixing, the premixing time is 2-3 minutes, then send it into the gunning equipment, add the remaining amount of polyaluminium oxalate sol at the discharge port, mix it, and gunning maintenance is carried out on the parts with more serious erosion of the iron ditch to extend the service life of the iron ditch; after the construction is completed, the baking operation is carried out immediately. When the repair thickness is within the range of 80-240mm, bake for 1-2 hours, and the temperature reaches above 800℃, and it can be used for iron. When the baking temperature is lower than 800℃, the baking degree of the repair material will be incomplete, causing the boiling of molten iron and excessive temperature drop. If the baking temperature is too high, the baking time will be extended, affecting the production rhythm of small and medium-sized blast furnaces.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] 1) The repair material of the present invention is beneficial to the rational use and protection of resources such as bauxite due to the addition of blast furnace slag, which alleviates the trend of gradual scarcity of non-renewable mineral resources and reduces the energy and environmental protection problems caused by mining; compared with bauxite and corundum, blast furnace slag can not only save energy, but also help reduce air pollution and carbon emissions, reduce the cost of refractory materials, and has good social and economic benefits.
[0028] 2) The repair material of the present invention uses modified asphalt and carbon black as carbon sources, which effectively reduces the environmental pollution and occupational health risks of operators caused by the baking process and is eco-friendly; at the same time, nano-scale carbon black has better dispersibility, which is more conducive to improving the strength and corrosion resistance of the repair material.
[0029] 3) The repair material of the present invention uses alumina micropowder with a wide particle size range and a large specific surface area, which not only significantly increases the plasticity and viscosity of the repair material, but also increases the sintering of the repair material at high temperatures, improves high temperature performance, and prolongs service life.
[0030] 4) The repair material of the present invention uses polymerized aluminum oxalate sol as a binder, which has high concentration and high viscosity. Compared with other sols and cements, it can reduce the free water and structural water in the material and significantly improve the bonding strength of the material; it has good affinity for aqueous solutions, which enhances the adhesion of the repair material and makes the repair material have good bonding with the thermal trench lining; it has good stability and does not require the addition of a water reducer. After dehydration, it can form a stable three-dimensional network structure, which enhances the stability of the repair material and extends its service life.
[0031] 5) The repair material of the present invention uses explosion-proof fibers with low melting point, good dispersibility and corrosion resistance, and has little effect on the fluidity of the castable. It can effectively solve the baking cracking problem, shorten the baking time, and achieve rapid baking. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as a limitation of this patent and is only used as an example.
[0033] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0034] The specific process of the embodiment of the present invention is:
[0035] An eco-friendly blast furnace iron groove hot repair material, the raw materials of the repair material include a main material and added explosion-proof fibers and polymerized aluminum oxalate sol; the main material includes the following raw materials in terms of weight percentage: 15-23% blast furnace slag, 34-60% fused reinforced corundum, 12-20% silicon carbide, 1-5% modified asphalt, 2-6% carbon black, 7-10% alumina powder, 1.5-3% metal aluminum powder, and 1.5-3% metal silicon powder; based on the weight of the main material, the explosion-proof fibers account for 0.04-0.12% of the weight of the main material, and the polymerized aluminum oxalate sol accounts for 10-16% of the weight of the main material.
[0036] A method for preparing and using an eco-friendly blast furnace iron groove hot repair material, comprising:
[0037] Preparation of dry materials: according to the composition and content of the raw materials, the ingredients are prepared. First, the matrix material with a particle size of less than 0.088 mm and the explosion-proof fiber are uniformly mixed for 2 to 3 minutes, and then the mixed matrix material is added to the aggregate with a particle size of more than 0.088 mm, stirred for 3 to 5 minutes, and then packed in half-ton bags for standby use;
[0038] When in use, first pour the dry material into the mixer, add 3-4% polymerized aluminum oxalate sol for premixing, the premixing time is 2-3 minutes, then send it to the spraying equipment, add the remaining amount of polymerized aluminum oxalate sol at the discharge port, and after mixing, spray the iron groove to the part with more serious erosion for maintenance; after the construction is completed, bake it immediately. When the repair thickness is within the range of 80-240mm, bake it for 1-2 hours, and the temperature reaches above 800℃, so it can be used for iron.
[0039] The present invention controls the particle size and addition amount of blast furnace iron slag, electric melting reinforced corundum, silicon carbide, modified asphalt, carbon black, alumina micropowder, metal aluminum powder, and metal silicon powder, and adds polymerized aluminum oxalate sol and explosion-proof fiber, as well as process parameters such as uniform mixing time, premixing time and baking system, so as to prepare an eco-friendly blast furnace iron ditch hot repair material which has the characteristics of being friendly to the ecological environment, having good adhesion, and good bonding with the hot ditch lining, being able to be quickly baked without bursting, having high strength and good overall performance during use, excellent slag erosion resistance, long service life, and having significant social and economic benefits.
[0040] The polymerized aluminum oxalate sol can be purchased commercially or obtained according to the preparation method described in patent CN117733064A.
[0041] Table 1 is a list of the raw material addition amounts of various embodiments and comparative examples of the present invention.
[0042] Table 2 shows the main process parameters of various embodiments and comparative examples of the present invention.
[0043] Table 3 is a table of performance test results of various embodiments and comparative examples of the present invention.
[0044] Table 1 (Wt, %)
[0045]
[0046] Table 2
[0047]
[0048] Table 3
[0049]
[0050]
[0051] As shown in Examples 1 to 5 of Tables 1 and 2, by adding the raw materials in the specified amounts and particle sizes in the present invention, appropriate amounts of blast furnace slag, electric fused reinforced corundum, silicon carbide, modified asphalt, carbon black, alumina powder, metal aluminum powder, metal silicon powder, as well as polymerized aluminum oxalate sol and explosion-proof fiber are added to the repair material, and at the same time, the process parameters such as the mixing time, stirring time, premixing time and baking system are well controlled. In this way, an eco-friendly blast furnace iron ditch hot repair material can be prepared, which has the characteristics of being friendly to the ecological environment, having good adhesion and good bonding with the hot ditch lining, being able to be quickly baked without bursting, having high strength and good overall performance during use, excellent resistance to slag erosion, long service life, and having significant social and economic benefits.
[0052] In contrast, for Comparative Examples 1 to 3 in which the amount of raw materials added, the production process and the baking system were not controlled, the repair materials could not simultaneously possess good ecological properties, adhesion, good bonding with the hot trench lining, the ability to be quickly baked without cracking, high strength during use, good overall performance, excellent resistance to slag erosion, and long service life, and could not meet the construction, baking and use performance of the product.
[0053] According to the description of the present invention, those skilled in the art can easily manufacture or use the eco-friendly blast furnace iron groove hot repair material and the preparation and use method thereof of the present invention, and can produce the positive effects recorded in the present invention.
[0054] The above is only a preferred embodiment of the present invention, but the present invention is not limited to the above specific embodiments. Those skilled in the art may make some modifications, supplements or use similar methods instead without departing from the principle of the present invention, which should also be regarded as the protection scope of the present invention.
Claims
1. An eco-friendly blast furnace iron channel hot repair material, characterized by: The raw materials of the repair material include main material and added explosion-proof fiber and polymerized aluminum oxalate sol; The main material includes the following raw materials by weight percentage: 15-23% blast furnace slag, 34-60% fused reinforced corundum, 12-20% silicon carbide, 1-5% modified asphalt, 2-6% carbon black, 7-10% alumina powder, 1.5-3% metal aluminum powder, and 1.5-3% metal silicon powder; Based on the weight of the main material, the explosion-proof fiber accounts for 0.04-0.12% of the weight of the main material, and the polymerized aluminum oxalate sol accounts for 10-16% of the weight of the main material.
2. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The main material includes the following raw materials by weight percentage: 15% blast furnace slag, 54% fused reinforced corundum, 15% silicon carbide, 1.5% modified asphalt, 3% carbon black, 8% alumina powder, 2% metal aluminum powder, and 1.5% metal silicon powder; The explosion-proof fiber accounts for 0.06% of the weight of the main material, and the polymerized aluminum oxalate sol accounts for 12% of the weight of the main material.
3. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The mass percentage of CaO in the blast furnace slag is 38-42%, the mass percentage of SiO2 is 30-35%, the mass percentage of Al2O3 is 14-17%, and the mass percentage of MgO is 6-9%; the particle size range of the blast furnace slag includes 3mm≤particle size≤5mm and 1mm≤particle size≤3mm, among which the blast furnace slag with 3mm≤particle size≤5mm accounts for 25-30% of the total mass of the blast furnace slag, and the blast furnace slag with 1mm≤particle size≤3mm accounts for 40-50% of the total mass of the blast furnace slag.
4. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The mass percentage of Al2O3 in the fused corundum is ≥92%, and the mass percentage of TiO2 is 3-5%; the particle size range of the fused corundum includes 1mm≤particle size≤3mm, 0.088mm≤particle size≤1m and 0mm≤particle size≤0.088mm, among which the fused corundum with 1mm≤particle size≤3mm accounts for 28-36% of the total mass of the fused corundum, the fused corundum with 0.088mm≤particle size≤1mm accounts for 23-30% of the total mass of the fused corundum, and the fused corundum with 0mm≤particle size≤0.088mm accounts for 34-49% of the total mass of the fused corundum.
5. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The mass percentage of SiC in the silicon carbide is ≥97%, and the silicon carbide particle size range includes 0.088mm≤particle size≤1mm and particle size≤0.088mm, wherein the silicon carbide with 0.088mm≤particle size≤1mm accounts for 30-50% of the total mass of the silicon carbide, and the silicon carbide with particle size≤0.088mm accounts for 50-70% of the total mass of the silicon carbide.
6. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The bulk density of the modified asphalt is 1.05-1.15 g / cm 3 , viscosity is 20~40Pa·s, softening point is 105~120℃, flash point ≥230℃, coking value ≥54%, particle size 0.088mm≤≤0.5mm.
7. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The mass percentage of C in the carbon black is ≥99%, the particle size of the carbon black is 10nm≤particle size≤100nm, and the specific surface area is greater than 1000m 2 / g.
8. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The mass percentage of Al2O3 in the alumina micropowder is ≥99.5%, the d50 of the alumina micropowder is 4.2 μm, d10 is 1.1 μm, d90 is 12.1 μm, and the typical specific surface area is 10.8 m 2 / g.
9. The eco-friendly blast furnace iron channel hot repair material according to claim 1, characterized in that: The explosion-proof fiber is polyethylene fiber with a melting point of 100-120° C. and a length of less than 6 mm. The main structure of the polymerized aluminum oxalate sol is aluminum oxycarboxylate, and the mass percentage of Al2O3 is greater than 30%.
10. A method for preparing and using the eco-friendly blast furnace iron channel hot repair material according to any one of claims 1 to 9, characterized in that: include: Preparation of dry materials: according to the composition and content of the raw materials, the ingredients are prepared. First, the matrix material with a particle size of less than 0.088 mm and the explosion-proof fiber are uniformly mixed for 2 to 3 minutes, and then the mixed matrix material is added to the aggregate with a particle size of more than 0.088 mm, stirred for 3 to 5 minutes, and then packed in half-ton bags for standby use; When in use, first pour the dry material into the mixer, add 3-4% polymerized aluminum oxalate sol for premixing, the premixing time is 2-3 minutes, then send it to the spraying equipment, add the remaining amount of polymerized aluminum oxalate sol at the discharge port, and after mixing, spray the iron groove to the part with more serious erosion for maintenance; after the construction is completed, bake it immediately. When the repair thickness is within the range of 80-240mm, bake it for 1-2 hours, and the temperature reaches above 800℃, so it can be used for iron.